The Third Migration - Daniel Talesnik (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This essay describes a migration scenario of architects in the interwar period, one that is different from others of the epoch. The Third Migration addresses a movement of mostly left-wing architects from Europe to the Soviet Union during the interwar period, architects that mostly relocated before the war, and many returned to Europe after the war. The Third Migration points towards a third paradigm of migration and not a chronological sequence, the first example being the Le Corbusier school around the world, and the second example being the Bauhaus that goes to the United States with Walter Gropius, Mies van der Rohe et alli. This larger frame helps to situate the specific group of architecture students from the German Bauhaus who followed Meyer to the Soviet Union in 1930 after he was expelled from the directorship of the Bauhaus: the so-called Red Bauhaus Brigade. This essay questions whether the movements of this Third Migration can be considered global and suggests a frame for analyzing the dissemination of modern architecture.